1995
DOI: 10.1055/s-0038-1653794
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Neutralizing Effects of Protamine on Unfractionated and Low Molecular Weight Heparin (Fragmin®) at the Site of Activation of the Coagulation System in Man

Abstract: SummaryIn a double-blind, randomized, cross-over study the neutralizing action of protamine towards unfractionated heparin (UFH, 150 U/kg i.v.) and a low molecular weight heparin (LMWH, Fragmin®, 100 anti-Xa U/kg i.v.) was investigated in 15 healthy subjects in vitro by measuring activated partial thromboplastin time (APTT), thrombin time (TT) and anti factor Xa activity (anti-Xa) in venous blood and in vivo by determination of prothrombin fragment 1.2 (f1.2) and thrombin-antithrombin III complexes (TAT) in ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
77
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 26 publications
1
77
1
1
Order By: Relevance
“…Related to this, PS can neutralize heparin-induced anti-IIa prolongation of clotting more quickly than heparin-induced anti-Xa prolongation of clotting [16,17].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Related to this, PS can neutralize heparin-induced anti-IIa prolongation of clotting more quickly than heparin-induced anti-Xa prolongation of clotting [16,17].…”
Section: Introductionmentioning
confidence: 94%
“…There is some disagreement over proper protamine dosing for heparin neutralization [12,14,17,18]. However, it appears that effective protamine dosing for heparin neutralization is about 1 mg/100U of unfractionated H, but should not be lower [17].…”
Section: Isrn Cell Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…14 On the other hand, protamine, a purified mixture of proteins obtained from fish sperm, neutralizes heparin and LMW-H by forming a stable complex that lacks anticoagulant activity. 15 Protamine is also in clinical use to reverse the anticoagulant activity of heparin following cardiopulmonary bypass and in cases of heparin-induced bleeding. 16 We previously prepared water-insoluble particles (10 µm in diameter) by mixing nonanticoagulant heparin and chitosan and by mixing of fucoidan and chitosan, and investigated the capacity of the resulting insoluble fucoidan/chitosan microparticles to protect activity of fibroblast growth factor-2 (FGF-2).…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the LMWP-conjugated growth factor combination generated more compact nanocomplexes by adding them to LMWH than did the native growth factors; this might have been due to further electrostatic interactions between the oppositely charged polyelectrolytes of LMWH and LMWP. 38 In addition, the LMWP-conjugated growth factor nanocomplex resulted in significantly accelerated wound closure compared with the LMWP-conjugated growth factor combination -it may be that the LMWP-conjugated growth factors were protected from rapid elimination by proteolytic inactivation, and that binding to their receptors was facilitated. 39 Whereas, the native growth factors also formed nanocomplexes after combining with LMWH, the native growth factor complexes failed to exhibit wound-healing efficacy.…”
mentioning
confidence: 99%